2001
DOI: 10.1002/ejsp.49
|View full text |Cite
|
Sign up to set email alerts
|

Social support in a changing Europe: an analysis of three post‐communist nations

Abstract: Despite the continuing interest in social transitions among social scientists, there has been little analysis of the impact of societal change on personal relationships. One important factor in helping individuals deal with the stresses associated with rapid transitions is social support. In our ®rst study, 450 manual workers, students and entrepreneurs in Russia, Georgia and Hungary completed structured questionnaires assessing demographic and value predictors of the perception of support availability and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 45 publications
0
5
0
2
Order By: Relevance
“…This scale has been shown to have high internal reliability in a wide range of cultures (e.g. Goodwin, Nizharadze, Nguyen Luu, & Emelyanova, 2001) and has been widely used in studies of ethnicity and culture (Vaux, 1985). Overall reliability indices are typically around .90 for the full scale and from .70 to .80 for its subscales (Wills & Shinar, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…This scale has been shown to have high internal reliability in a wide range of cultures (e.g. Goodwin, Nizharadze, Nguyen Luu, & Emelyanova, 2001) and has been widely used in studies of ethnicity and culture (Vaux, 1985). Overall reliability indices are typically around .90 for the full scale and from .70 to .80 for its subscales (Wills & Shinar, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…It is well known that values provide a lens through which people perceive and interpret social reality, and that people who endorse certain values are likely to see the world in a specific way. For instance, Goodwin, Nizharadze, Luu, Kosa, and Emelyanova (2001) found that values predicted people's perceived availability of social support in three post-Communist nations. Reciprocally, cognitions also influence the goals that people pursue.…”
Section: Social Axioms and Value Typesmentioning
confidence: 99%
“…2 Goodwin et al (2001), Lokshin and Yemtsov (2001), Lokshin et al (2000), Lonkila (1999Lonkila ( , 1997, Dershem andGzirishvili (1998), andSik (1995) discuss this argument applied to Russia,Georgia,and Hungary. 3 See for example Bongaarts and Watkins (1996) or Kohler et al (2001) for elaborating the relevance of diffusion processes and communication networks for the increasing use of contraceptives in developing countries.…”
Section: Social Capital and Relationships Of Reciprocal Exchangementioning
confidence: 99%